Efficacy of RADA16-Based Self-Assembling Peptides on Wound Healing: A Meta-Analysis of Preclinical Animal Studies - Jiaju Lu; Liuting Chen; Zeyue Sun; Zhimou Yang (Pharmaceuticals)
Objectives: This analysis aims to provide evidence supporting the feasibility of clinical application of self-assembling peptides for skin wound healing. Methods: This review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. PubMed, Web of Science, and Cochrane Library were searched (up to June 17, 2024). The primary outcome, wound closure rate at 7 and 14 days post-injury, was pooled using a random-effects meta-analysis. The risk of bias (ROB) assessment and meta-analysis were performed using the Systematic Review Centre for Laboratory animal Experimentation (SYRCLE)’s ROB tool for animal studies and RevMan software. Results: A total of 502 unique records were identified from our search, with 12 experimental animal studies meeting the prespecified inclusion criteria (n = 272 animals). The RADA16 interventions promoted wound closure rate compared to controls (saline or no treatment group) in both diabetic and non-diabetic animal models (Mean Difference (MD) = 11.25, 95% Confidence Interval (CI): 5.73 to 16.78, p < 0.0001; MD = 9.48, 95% CI: 4.75 to 14.22, p < 0.0001 at 7 and 14 days post-injury, respectively). Healing was further enhanced using RADA16-based functional self-assembling peptides compared to RADA16 group in both diabetic and non-diabetic animal models (MD = 27.25, 95% CI: 22.68 to 31.83, p < 0.00001; MD = 29.11, 95% CI: 24.30 to 33.91, p < 0.00001 at 7 and 14 days after injury, respectively). The ROB was uncertain for most studies due to insufficient reporting. Conclusions: RADA16-based self-assembling peptides, particularly those modified with functional peptide motifs, represent a promising treatment for non-diabetic and diabetic wounds in pre-clinical studies, and translation to the clinical domain appears warranted.